Fostering creativity (Harvard Business Press, 2010)
Every day on the job, you face common challenges. And you need immediate solutions to those challenges. The Pocket Mentor Series can help. Each book in the series is packed with handy tools, self-tests, and real-life examples to help you identify your strengths and weaknesses and hone critical skills. Whether you're at your desk, in a meeting, or on the road, these portable, concise guides enable you to tackle the daily demands of your work with speed, savvy, and effectiveness